Transfer Pricing and Tax Avoidance: Does Sales Growth Matter? - I Made Dwi Sumba Wirawan; Desak Ruric Pradnya Paramitha Nida (Universitas Muhammadiyah Makassar, 2025)
This study examines the relationship between sales growth, transfer pricing, and corporate tax avoidance strategies. Specifically, it explores how changes in sales growth affect multinational corporations' use of transfer pricing to reduce tax liabilities. Using a comprehensive dataset of multinational enterprises, the study applies an econometric model to identify the direct and indirect effects of sales growth on tax avoidance via transfer pricing. The sample consists of manufacturing companies in the food and beverage industry sub-sector listed on the Indonesia Stock Exchange. Purposive sampling was used for this study. In summary, despite transfer pricing being common among multinational corporations, this study finds no statistically significant direct impact on tax avoidance. Moreover, sales growth shows no moderating effect on this relationship. These findings highlight the complexity of identifying simple linear relationships and suggest the need for further research into how regulatory environments, firm-specific strategies, and macroeconomic factors influence the link between transfer pricing, sales growth, and tax avoidance.